Safety of oil from Schizochytrium limacinum (strain ATCC‐20889) for use in infant and follow‐on formula as a novel food pursuant to Regulation (EU) 2015/2283 - EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA); Dominique Turck; Torsten Bohn; Montaña Cámara; Jacqueline Castenmiller; Stefaan De Henauw; Karen Ildico Hirsch‐Ernst; Ángeles Jos; Alexandre Maciuk; Inge Mangelsdorf; Breige McNulty; Androniki Naska; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on the safety of an oil derived from the microalga Schizochytrium sp. (strain ATCC‐20889) as a novel food (NF) pursuant to Regulation (EU) 2015/2283. The NF is a mixture of triglycerides in which docosahexaenoic acid (DHA) represents 40%–43% of fatty acids. The available evidence indicates that the source organism (strain ATCC‐20889) belongs to the species Schizochytrium limacinum. The applicant intends to market the NF as an ingredient in infant formulae (IF) and follow‐on formulae (FOF). The use levels proposed by the applicant were derived from Regulation (EU) 2016/127, which states the mandatory presence of DHA to IF and FOF at the levels of 20–50 mg/100 kcal. Schizochytrium limacinum was attributed the qualified presumption of safety (QPS) status with the qualification ‘for production purposes only’. Data provided by the applicant demonstrated the absence of viable cells in the NF. No toxicological studies were performed with the NF. However, based on the available toxicological data on oils derived from Schizochytrium sp., the QPS status of the source of the NF, the production process, the composition of the NF, the absence of marine biotoxins and viable cells in the NF, the Panel considers that there are no concerns with regard to the toxicity of the NF. The Panel concludes that the NF is safe under the proposed conditions of use.